Soluble Molybdenum Reduction by Morganella sp. Locally-isolated from Agricultural Land in Kano (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
Intensive agriculture and industrial activities have significantly increased the global burden of pollutants; thus, bioremediation of these pollutants is intensely sought. A bacterium with potential of reducing toxic soluble molybdenum to precipitable molybdenum blue (Mo-blue) was isolated from agricultural soil in Darmanawa, Kano state. The bacterium grown on low phosphate media (LPM) reduces molybadate to Mo-blue optimally at pH between 6.0 and 7.5, temperature of 35 Â°C, glucose was the best electron donor source at 5 g/L and ammonium sulphate was the best nitrogen source. The optimum molybdate concentration supporting the reduction process was 40 mM at 3.5 mM phosphate. Phylogenetic analysis of 16S rRNA partial sequence identified the bacterium as Morganella sp. The ability of this isolate to reduce toxic soluble molybdenum to colloidal less toxic form is novel and makes the bacterium an important instrument for bioremediation of this pollutant.
Keywords: Pollution; molybdenum; toxicity; Morganella; Kano